2020
DOI: 10.1371/journal.pone.0236052
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of oral HIV self-testing among female sex workers in Gaborone, Botswana

Abstract: Background HIV prevalence among female sex workers (FSW) in sub-Saharan Africa is much higher than in the general population. HIV self-testing (HIVST) may be useful for increasing testing rates in FSW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Selecting the appropriate mode of kit distribution was important to ensure accessibility and adoption [57,78,90,92,99,104,105,108,110,112,119,122,137,139,141,163,184,189,190,202,204]. Modes of distribution described include: (1) direct delivery by community health workers, peers, partners, and sex workers, (2) Home delivery, and (3) Pick up at health facilities or community-based organizations or other sites (e.g., health clubs, markets, private pharmacies, vending machines).…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
“…Selecting the appropriate mode of kit distribution was important to ensure accessibility and adoption [57,78,90,92,99,104,105,108,110,112,119,122,137,139,141,163,184,189,190,202,204]. Modes of distribution described include: (1) direct delivery by community health workers, peers, partners, and sex workers, (2) Home delivery, and (3) Pick up at health facilities or community-based organizations or other sites (e.g., health clubs, markets, private pharmacies, vending machines).…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
“…Some studies have also concluded that FSW may require some form of training in order for then to correctly perform unassisted HIV self-testing [ 37 ]. In Botswana, we previously conducted a qualitative study among FSW in Gaborone to explore the acceptability of HIV self-testing and of secondary distribution of HIV self-test kits [ 38 ]. The qualitative study showed that, despite having no prior knowledge of HIV self-testing, female sex workers in Gaborone perceived it to be a highly acceptable method of HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…The research signaled the need for addressing identified structural barriers in the healthcare system in the implementation of HIV self-testing. It further highlighted the importance of having a FSW peer-driven approach when implementing self-testing in this key population, with some oversight and guidance from healthcare professionals [ 38 ]. The actual uptake of HIV self-testing has not been evaluated in FSW in Botswana, who are at increased risk for HIV [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the acceptability of HIVST, which includes both oral fluid test (OFT) and blood-based kits, has been studied among key populations, the studies are overwhelmingly performed among MSM in high-income countries and with varied types of supervisions [ 17 - 22 ]. However, the studies performed among FSWs demonstrated HIVST as a highly accepted strategy [ 21 , 23 - 26 ], which is a promising alternative to facility-based HIV testing.…”
Section: Introductionmentioning
confidence: 99%